Cardiac Tumors: Echocardiographic Diagnosis and Forensic Correlations. (December 2016) - Capotosto, Lidia; Elena, Giulia; Massoni, Francesco; De Sio, Simone; Carnevale, Aldo; Ricci, Serafino; Vitarelli, Antonio
Abstract : Abstract: In the past, cardiac tumors were a just clinical curiosity and the prognosis was poor. Surgical management became possible after the advent of cardiopulmonary bypass, and more recently, preoperative diagnosis was greatly improved by the development of echocardiography, computed tomography, and magnetic resonance imaging. The value of echocardiography for diagnosing cardiac mass lesions has become well established. Numerous advances have occurred in the last 5 decades, and the evolution of echocardiography involves the development of its many modalities. This review is intended to help echocardiologists and forensic pathologists in providing good medical practice when faced with the challenge of investigating unexpected clinical signs, particularly in young people, or unexpected postmortem findings.